The Moschcowitz operation as a therapeutic method in case of enterocoele - Dyrda, Adam; Nazar, Dominika (Menopause Review/Przegląd Menopauzalny, 2006)
Our objective was to present the case of patient with iatrogenic enterocoele after the Manchester operation performed 3 years ago due to pelvic organ prolapse. The pouch of Douglas was successfully obliterated with the Moschcowitz culdoplasty via abdominal approach.The patient was examined 4 weeks following surgery. She has reported no symptoms associated with enterocoele. In gynecological examination there was no reccurence of descensus of the vagina.